Female cancer survivors are more likely to be at high risk of malnutrition and meet the threshold for clinical importance for a number of quality of life subscales. Issue 5 (24th March 2021) - Keaver, Laura; O'Callaghan, Niamh; O'Sullivan, Aoibheann; Quinn, Laoise; Loftus, Amy; McHugh, Catherine M.
Abstract: Background: The present study aimed to explore malnutrition risk, handgrip strength and quality of life (QOL) in cancer survivors. Methods: In total, 232 individuals completed a demographic questionnaire, Patient‐Generated Subjective Global Assessment Short Form and the European Organization for Research and Treatment of Cancer QOL Questionnaire (EORTC QLQ‐C30). Handgrip strength was determined using a spring‐loaded handgrip dynamometer and anthropometric measurements were taken by an oncology nurse. Frequencies and distribution data, analysis of variance and chi‐squared tests were then conducted. Results: The majority of the cohort were female ( n  = 141; 60.8%) had breast cancer ( n  = 62; 26.7%) and the mean ± SD body mass index (BMI) was 26.6 ± 6.2 kg m –2 . Less than a one‐third reported seeing a dietitian ( n  = 68; 29.3%). Over one‐third reported recent weight loss ( n  = 88; 37.3%). Some 40.9% ( n  = 95) were at moderate to high risk of malnutrition, with women more likely than men to be classified as high risk ( p  < 0.05). Mean ± SD handgrip strength was 25 ± 15 kg and this differed significantly by gender ( p  = 0.00), cancer type ( p  = 0.01) and BMI classification ( p  = 0.01). One‐fifth of individuals were classified as having dynapenia ( n  = 48; 21.1%). Median (interquartile range) QOL score was 66.7 (33.3). The proportion of individuals meeting the threshold for clinical importance for QOL subscales ranged from 12.5% (constipation) to 42.7% (physical functioning). Females were more likely than males to meet the threshold for physical functioning ( p  = 0.00), fatigue ( p  = 0.02) and pain ( p  = 0.01). Conclusions: Females are more likely than males to be at high risk of malnutrition and meet the threshold for clinical significance for several QOL subscales. Abstract : Females living with and beyond cancer are more likely than males to be at risk of malnutrition and meet the threshold for clinical importance for a number of quality of life subscales.